Exploring the relationships among transformational leadership, teacher efficacy and teacher commitment in Malaysia secondary schools - Teh, Pei Ling; Lope Pihie, Zaidatol Akmaliah; Asimiran, Soaib; Foo, Say Fooi (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The purpose of this paper is to develop a conceptual model in exploring the relationships among transformational leadership, teacher efficacy and teacher commitment in Malaysia secondary school teachers. System theory, Transformational leadership theory, and Bandura’s social cognitive theory serve as a vessel in developing this conceptual paper. From the extensive literature review, six dimensions of transformational leadership (Kenneth Leithwood & Jantzi, 1997), three components of teacher efficacy (Tschannen-moran & William, 2001; Tschannen-Moran, Hoy, & Hoy, 1998) and teacher commitment (Meyer & Allen, 2004) are identified to construct the model. Path analysis will be carried out to identify the paths through transformational leadership to teacher efficacy, from teacher efficacy to teacher commitment and also from transformational leadership to teacher commitment. An insightful for the analysis of the relationships among transformational leadership, teacher efficacy and teacher commitment will be viewed. This design stands in contrast to other researchers’ study by using Structural Equation Modelling (SEM) as the analysis tool.